2009
DOI: 10.1530/rep-09-0091
|View full text |Cite
|
Sign up to set email alerts
|

Follicle and hormone dynamics in single versus double ovulating heifers

Abstract: Follicles R5 mm were ablated at 4 day post-ovulation in heifers to induce a follicular wave, and prostaglandin F 2a was given at day 6 to increase the incidence of double ovulations. Follicle diameters and plasma hormone concentrations were compared between single ovulators (nZ12) and double ovulators (nZ8). In double ovulators, the interval from follicle deviation to the peak of the pre-ovulatory LH surge was shorter (1.9G0.2 vs 2.5G0.2 days; P!0.02) and diameter of the largest pre-ovulatory follicle was smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 40 publications
4
16
0
2
Order By: Relevance
“…The intra-and interassay coefficients of variation (CV) and sensitivity were 6.1%, 6.3% and 0.01 ng/ml respectively. Plasma LH and FSH concentrations were assayed by RIAs as described for cattle (Bolt et al 1990) with validations and modifications as reported by our laboratory for LH (Ginther et al 1999) and FSH (Adams et al 1992) and with further recent modifications as reported for both assays (Palhao et al 2009). The intra-and interassay CV and sensitivity respectively were 9.2%, 10.5% and 0.03 ng/ml for LH and 6.5%, 4.8% and 0.07 ng/ml for FSH.…”
Section: Blood Sampling and Hormone Assaysmentioning
confidence: 99%
“…The intra-and interassay coefficients of variation (CV) and sensitivity were 6.1%, 6.3% and 0.01 ng/ml respectively. Plasma LH and FSH concentrations were assayed by RIAs as described for cattle (Bolt et al 1990) with validations and modifications as reported by our laboratory for LH (Ginther et al 1999) and FSH (Adams et al 1992) and with further recent modifications as reported for both assays (Palhao et al 2009). The intra-and interassay CV and sensitivity respectively were 9.2%, 10.5% and 0.03 ng/ml for LH and 6.5%, 4.8% and 0.07 ng/ml for FSH.…”
Section: Blood Sampling and Hormone Assaysmentioning
confidence: 99%
“…É importante ter cautela para interpretar esses dados, uma vez que o estradiol utilizado para regredir o FD no início do protocolo também atua como supressor de FSH, que atua no desenvolvimento da nova onda folicular (PALHAO et al, 2009). …”
Section: Discussionunclassified
“…Como o pico de LH causa elevação do fluxo sanguíneo na parede do folículo ovulatório (Acosta, 2007), é possível correlacionar este fato com uma maior sincronia dos animais tratados com BE como indutor ovulatório. Outra evidência da maior sincronia dos animais neste grupo foi o menor diâmetro do folículo ovulatório, uma vez que o crescimento folicular se reduz após o pico de LH (Palhao et al, 2009). …”
Section: Discussionunclassified
“…The plasma was decanted and stored (À20 C) until assayed. The RIA for FSH assay has been validated and described for bovine plasma in our laboratory [15]. The intra-assay and interassay coefficients of variation and sensitivity for experiment 1 were 10.2%, 10.9%, and 0.02 ng/mL.…”
Section: Heifers Blood Samples and Fsh Assaymentioning
confidence: 99%